Deciphering the worlds of Hebrews collected essays - Gelardini, Gabriella 1964- (Boston BRILL, 2021)
In Deciphering the Worlds of Hebrews Gabriella Gelardini gathers fifteen essays on Hebrews that deal with topics such as structure and intertext, sin and faith, atonement and cult, as well as space and resistance.
Intro -- Contents -- Introduction -- 1 Hebrews Scholarship in the Nineteenth and Twentieth Centuries -- 2 Hebrews Scholarship in the Twenty-First Century -- 3 Arrangement and Content of This Collection -- Part 1 The World of Hebrews's Text -- Chapter 1"As if by Paul?" Some Remarks on the Textual Strategy of Anonymity in Hebrews -- 1 Introduction-Hebrews: Pauline or not Pauline, or "Somehow" Connected to a Pauline Environment -- 2 Anonymity as a Literary Strategy -- 3 Habakkuk 2:4 in Hebrews and Paul -- 4 Jesus as Mercy Seat (ἱλαστήριον) in Heb 9:5 and in Rom 3:25? -- 5 Once for All (ἐφάπαξ) in Hebrews and Paul -- 6 Brief Conclusion -- Chapter 2 From "Linguistic Turn" and Hebrews Scholarship to Anadiplosis Iterata: The Enigma of a Structure -- 1 History of Ideas -- 1.1 Linguistic Turn -- 1.2 Structuralism -- 1.3 Poststructuralism -- 1.4 Cultural Turn -- 2 Hebrews Scholarship in the Twentieth and Twenty-First Centuries -- 2.1 History -- 2.2 Methods -- 2.3 Structures -- 2.4 Main Theological Emphases -- 3 Structural Analysis: A New Proposal -- 3.1 Method -- 3.2 Macrostructure of Hebrews -- 3.3 Microstructure of Hebrews 3:1-6:20 -- 3.4 Main Theological Emphasis and Interpretation -- Chapter 3 Hebrews, Homiletics, and Liturgical Scripture Interpretation -- 1 The Ancient Synagogue and Its Liturgy -- 2 The Ancient Synagogue Homily -- 3 The Two Readings Underlying Hebrews, or Its Two Central Scriptural Quotations -- 4 Hebrews, an Ancient Synagogue Homily and Its Remaining Scriptural Quotations -- 5 Hebrews in the Context of Ancient Synagogue Liturgy -- Chapter 4 Hebrews, an Ancient Synagogue Homily for Tisha be-Av: Its Function, Its Basis ,Its Theological Interpretation -- 1 Introduction -- 2 The Ancient Synagogue Homily in Its Liturgical Context -- 2.1 The Sitz im Leben of the Ancient Synagogue Homily: The Sabbath Gathering.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books